Hydrodynamic characteristics of the modified V-shaped Semi-floating offshore wind turbine with heave plates - Shi, Wei; Zhang, Lixian; You, Jikun; Karimirad, Madjid; Michailides, Constantine (My University, 2019)
In recent years, there is a great need to develop offshore wind energy on a global scale due to the greenhouse effect and energy crisis. Great efforts have been devoted to developing a reliable floating offshore wind energy technology to take advantage of the large amount of wind energy resources that exist in deep water. In this paper, a novel concept of a floating offshore wind turbine (FOWT), namely, the modified V-shaped semi-floating with heave plate, is proposed, and its hydrodynamic characteristics are studied. A numerical model based on ANSYS/AQWA is used to investigate the dynamic motion, response characteristics and mooring performance of the new concept. Moreover, the response amplitude operators (RAOs) of the different response quantities are also elaborated. A comparative study of the dynamic response of the different response quantities of the modified V-shape and original V-shaped semi-floating is carried out for operational environmental conditions. It is found that the modified V-shape semi-floating shows relatively better performance in platform motion and mooring line response.
Keywords: Floating offshore wind turbines (FOWT); Hydrodynamic characteristics; Off-shore wind energy; Response amplitude operator; Response characteristic